Digital sustainable innovations in rural areas. - Kruppenbacher, Viktoria (Nomos, 2019)
In rural areas the achievement of sustainability is associated with some special aspects. Due to social developments like demographic change and urbanization, rural areas should increase their attractiveness especially for young people and companies. Otherwise, economic development as well as social and environmental aspects with regard to sustainability suffer. Furthermore, sustainable farming is relevant for rural areas. Digitization offers opportunities to address the challenges appearing in rural areas. There are already many specific digital innovations that will eventually contribute to sustainable development. In this chapter, the analysis of certain digital innovations examines their contribution to certain aspects of sustainability specifically for rural areas. For this purpose, experts were asked and digital innovations from the areas E-Health and Smart Farming and the project "Digitale Dörfer" were analysed with respect to their contribution to the Sustainable Development Goals. It has been shown that digital innovations influence sustainability of rural areas in several ways. Hence, digitization is able to generate a large potential for sustainability of rural areas that need to be generalized and further examined in future research.
Keywords: Ländlicher Raum; Digitalisierung; Kommunikationstechnologie; Standortfaktor; Nachhaltige Regionalentwicklung; E-Health; Smart Farming; Digitale Dörfer; Sustainable Development Goals